Cosmogenic records and noble gases in Mukundpura CM2.0 carbonaceous chondrite. (June 2022) - Mahajan, Ramakant R.; Raychaudhuri, D.; Dutta, A.; Shukla, Anil D.
Abstract: The Mukundpura carbonaceous chondrite represents the negligible thermally affected with modest aqueous altered chondrite, providing a new unique opportunity to investigate the composition of the early solar system materials. We investigated cosmogenic records using radioactive and stable isotopes in Mukundpura. The cosmic ray exposure (CRE) age of Mukundpura is estimated to be 6.54 ​± ​1.34 ​Ma based on cosmogenic 21 Ne by considering trapped noble gas as Q-gas. The exposure age determined from combination of radioactive isotope and neon yields a range between 5.9 and 6.5 ​Ma. The CRE age lies at the higher end of the CRE age distribution of the CM chondrite group, which is dominated by ages of 0.1–10 ​Ma. Noble gas isotope signature confirms the presence of multiple components, chondritic phase Q, HL from presolar grains and solar wind. Highlights: Cosmic ray exposure history of new carbonaceous chondrite Mukundpura is discussed. Mukundpura CM2.0 chondrite exhibit longer exposure history. Noble gas isotopic ratios indicate presence of multiple trapped components.